Does angina vary with the menstrual cycle in women with premenopausal coronary artery disease?. Issue 2 (1st August 2000) - Lloyd, G W; Patel, N R; McGing, E; Cooper, A F; Brennand-Roper, D; Jackson, G
Abstract : OBJECTIVE: To determine whether angina in women with established coronary heart disease varies with changes in hormone concentrations during the menstrual cycle. DESIGN: Subjects were prospectively studied once a week for four weeks. SETTING: Cardiology outpatient department of tertiary referral centre. SUBJECTS: Nine premenopausal women, mean (SEM) age 38.89 (2.18) years, with established coronary heart disease, symptomatic angina, and a positive exercise test. MAIN OUTCOME MEASURE: Myocardial ischaemia as determined by time to 1 mm ST depression during symptom limited exercise testing. Position in the menstrual cycle was established from hormone concentrations. RESULTS: The early follicular phase, when oestradiol and progesterone concentrations were both low, was associated with the worst exercise performance in terms of time to onset of myocardial ischaemia, at 290 (79) seconds; the best performance (418 (71) seconds) was when oestrogen concentrations were highest in the mid-cycle (p < 0.05). Similar trends were observed in other measured variables. Progesterone concentrations did not influence exercise performance. CONCLUSIONS: During the menstrual cycle myocardial ischaemia was more easily induced when oestrogen concentrations were low. This may be important for timing the assessment and evaluating treatment in women with coronary heart disease.